Poorly differentiated, ovarian Sertoli-Leydig cell tumor with heterologous rhabdomyosarcoma and glandular elements: Diagnosis and management of a rare neoplasm - Charanjeet Singh; Sarfraz Ahmad; Fouad M. Hajjar; Robert W. Holloway (Elsevier, 2018)
Ovarian Sertoli-Leydig cell tumors (SLCT) represent <2% of primary ovarian tumors, which range from benign to malignant; majority of the latter are low-grade. We present the case of a 12-year-old pre-pubertal female with poorly differentiated SLCT and heterologous rhabdomyosarcoma (FIGO stage-IA). She presented with worsening abdominal pain, pelvic mass, and elevated pre-operative serum Alpha-fetoprotein (AFP, 77.1 ng/mL). She underwent right salpingo-oophorectomy, omentectomy, and lymphadenectomy. The high-risk histology warranted 4-cycles of adjuvant BEP chemotherapy. There was no clinical evidence of recurrence at the 20-month follow-up. High-grade sex cord-stromal tumors are rare, present with low-stage disease, and have good progression-free survival following chemotherapy. Rarity of these tumors poses challenges in their diagnosis and treatment. Review of literature suggests that the presented case is youngest patient with dedifferentiated SLCT. Keywords: Sertoli-Leydig cell tumor, Rhabdomyosarcoma, AFP, Ovarian cyst, Literature review